High resolution physical analysis of ohmic contact formation at GaN-HEMT devices. (September 2017) - Graff, A.; Simon-Najasek, M.; Altmann, F.; Kuzmik, J.; Gregušová, D.; Haščík, Š.; Jung, H.; Baur, T.; Grünenpütt, J.; Blanck, H.
Abstract: A low ohmic contact resistance is a key request on AlGaN/GaN HEMT devices especially when dealing with higher frequency applications. In such a GaN material system very high annealing temperatures of up to 900 °C are frequently necessary to achieve low ohmic resistance. It is known that high annealing temperatures could reduce electrical performance and reliability of the devices. Therefore, low contact resistances at reduced annealing temperatures are beneficial. In the present work a special SiCl4 plasma treatment was applied prior to the ohm metallisation resulting in sufficiently low ohmic resistances at a significantly reduced anneal temperature of 750 °C. High resolution physical analysis by transmission electron microscopy (TEM) and time of flight secondary mass spectroscopy (TOFSIMS) have been performed to understand the structural and chemical differences between the treated ohmic contacts compared to contacts processed under standard conditions. An advanced preparation technique was developed to get access to the reaction interfaces for TOFSIMS analysis from backside. It could be shown that the SiCl4 treated samples reveal less impurities/contaminants on the ohmic metal–GaN/AlGaN interface and a different metal semiconductor alloying. The diffusion of metals like Al and Au into the semiconductor substrate was detected at the front of the TiN forming reaction. Highlights: SiCl4 treatment of the AlGaN surface reduces the temperature for contact formation. TOF-SIMS experiments from the backside show modified impurity distribution. Analytical TEM investigations reveal different structures at the contact interface. TiN intrusions with Al and Au at the diffusion front directly contact the 2DEG.